Tahap pengetahuan dan pola penggunaan perkhidmatan kerja sosial di kalangan pesakit: Kajian kes di Hospital UKM - Mohd Suhaimi Mohamad, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2007)
This article is based on a study that was conducted to assess the level of knowledge of patients who receive the medical social work services. The researcher assumes that the level of patient’s knowledge about the services offered at the Department of Medial Social Work (JKSP) which affects the possibility of service use. Even though the knowledge and services use were also determined by the patient’s demographic and socio-economic backgrounds. This study is considered to be important especially in helping the JKSP to determine the focus of services for the patient. Data obtained through interviews of 220 respondents who are patients at HUKM from January 2002 to December 2002. They consist of different ethnic groups, age, gender, education level, occupation and income. The result of the study found that the level of knowledge amongst patients in HUKM was moderate and it has a significant relationship with ethnicity, age, education level, income and employment status at the value of p <.05. Most of the referred patients have chronic diseases that required practical and financial assistance. Patterns of utilisation of social work services is still plagued by the view that the JKSP work merely as the welfare department although it offers a variety of other social work services which functioning to assist the recovery of patients and their families